2013
DOI: 10.3233/jad-121990
|View full text |Cite
|
Sign up to set email alerts
|

Slow Excitotoxicity in Alzheimer's Disease

Abstract: Abstract. Progress is being made in identifying possible pathogenic factors and novel genes in the development of Alzheimer's disease (AD). Many of these could contribute to 'slow excitotoxicity', defined as neuronal loss due to overexcitation as a consequence of decreased energy production due, for instance, to changes in insulin receptor signaling; or receptor abnormalities, such as tau-induced alterations in N-methyl-D-aspartate (NMDA) receptor phosphorylation. As a result, glutamate becomes neurotoxic at c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 282 publications
(279 reference statements)
2
57
0
Order By: Relevance
“…It is well established that increased Aβ can reduce the membrane potential, thus enhancing Ca 2+ influx, leading to an accumulation of Ca 2+ in cells, leading to excitotoxicity and cell death via apoptotic processes (Greenamyre, 1991; Harkany et al, 2000; Barger, 2004; Hynd et al, 2004; Tsai et al, 2005; Koutsilieri and Riederer, 2007). Increased oxidative stress may further interfere with Ca immobilization, leading to cell death via additional cytotoxic pathways (Esposito et al, 2013; Ong et al, 2013). It has been previously reported that Ca 2+ overload can modulate APP metabolism, and accelerate APP hydrolysis to generate more Aβ (Wang et al, 1994; Ye et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that increased Aβ can reduce the membrane potential, thus enhancing Ca 2+ influx, leading to an accumulation of Ca 2+ in cells, leading to excitotoxicity and cell death via apoptotic processes (Greenamyre, 1991; Harkany et al, 2000; Barger, 2004; Hynd et al, 2004; Tsai et al, 2005; Koutsilieri and Riederer, 2007). Increased oxidative stress may further interfere with Ca immobilization, leading to cell death via additional cytotoxic pathways (Esposito et al, 2013; Ong et al, 2013). It has been previously reported that Ca 2+ overload can modulate APP metabolism, and accelerate APP hydrolysis to generate more Aβ (Wang et al, 1994; Ye et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of this receptor has been associated with neurological disease including Alzheimer's disease (Hynd et al, 2004;Ong et al, 2013), multiple sclerosis (Kostic et al, 2013), autism (Essa et al, 2013), amyotrophic lateral sclerosis (Guo et al, 2003), and stroke (Hansen, 1995;Choi, 1998;Wang et al, 2010). Although human GLF poisoning cases are primarily from acute exposure, evidence suggests that GLF can produce chronic neurotoxic effects (Calas et al, 2008;Meme et al, 2009) or detrimentally impact the developing brain (Fujii et al, 1996;Watanabe, 1997).…”
Section: Relevance Of In Vitro Results To In Vivo Toxicitymentioning
confidence: 97%
“…Previous studies have suggested that iron may contribute to nervous system development in children; an iron deficiency during infancy has been shown to affect the development of the nervous system, leading to poor intelligence, a lack of concentration, learning difficulties and various other symptoms (4,6). Conversely, other studies have reported an increased brain iron content in various adult demyelinating diseases, including Alzheimer's disease, Parkinson's disease, Huntington's chorea (79) and obstructive cerebral hemorrhage (10,11). Notably, iron chelation therapy, including deferoxamine, is able to markedly alleviate these diseases (12).…”
Section: Introductionmentioning
confidence: 82%